Abstrahierendes Lernen durch aktive Modellbildung: Evaluation eines Prozesses und einer Lernumgebung - Till Schümmer; Wolfram Schobert; Christina Matschke; Joerg M. Haake (FernUniversität Hagen, 2015)
Experts and novices typically show different competencies in learning by abstraction. While novices typically consider the concrete example, experts often abstract from an example towards the underlying principles. This article presents a process and a computer-supported learning environment for learning through abstraction. An evaluation of the learning environment shows that pilot students were able to construct an abstract model from experience reports using the learning environment. The fewer common surface features the examples had, the easier was the abstraction. We also found that learners reflect on their learning process and adjusted the process to their specific learning preferences by following a modified process for learning through abstraction.